Toast ‘n’ Spread / Suhaila Athirah Mohd Yazid - Mohd Yazid, Suhaila Athirah (2020)
Our company Ezylife Sdn Bhd always produce a product that will make your everyday life easier. We have come up with a new product which is an innovated toaster that can toast and spread fillings on bread or waffles at once. It is called Toast ‘n’ Spread machine. We produce this product because normally people would choose bread over something else as their breakfast or snacks since it will make them full for a longer time. Nowadays, there are many people skipped their breakfast or cannot enjoy a proper meal even its just a slice of bread due to their busy schedules and routine. To them it takes a lot of time to switch on the toaster, open the jar of a jam or butter and spread it on breads. The hassleness of these things make them skipped their breakfast which is not good for their health. As we all know breakfast is an important meal of the day. This Toast ‘n’ Spread machine can solve these problems. They can enjoy toasted bread or waffles with fillings just by a few clicks on their phone without taking much of their time. Next, our target market will be focusing on working people, family especially urban area which is in Kuala Lumpur that are busy but want to have a decent meal for their family and a time conscious person who wants to save time. We also target offices and company, they can place this machine in the pantry, so their employees can have a healthy meal or snacks if they are hungry. Based on the specification of this product, the price is considered reasonable which is RM 140. The management team of our company are divided into several section and each section were led by experienced and professional employee to ensure our company’s product and efficiency.